Help solving a system of differential equations
3 Ansichten (letzte 30 Tage)
Ältere Kommentare anzeigen
Tejas Adsul
am 15 Mai 2018
Kommentiert: Tejas Adsul
am 16 Mai 2018
I have the following system of differential equations, and I am not able to understand the best way to go about them. I tried using a couple of functions like dsolve, ode45, etc., but most of them give errors that I am not able to understand.
x(1)=0.3; x(3)=0.9; y(1)=0.4; y(3)=0.8;
A=10; p=10;
syms X1 X2;
num = ((x(3)-X1)-(X1-x(1)))*X1 + ((y(3)-X2)-(X2-y(1)))*X2;
den = sqrt((x(3)-X1)-(X1-x(1))^2 + (y(3)-X2)-(X2-y(1))^2);
Em = -A*(X1-x(1))*(x(3)-X1) - A*(X2-y(1))*(y(3)-X2) + p*num/den;
dXdt = [-diff(Em,X1); -diff(Em,X2)];
I would like to get X1 and X2 as a function of time. If I define syms X1(t) and X2(t), I get the error 'All arguments, except for the first one, must not be symbolic functions.' The above code, when run, gives me expressions in terms of X1 and X2. I need solutions of X1 and X2 in terms of t, where dX1dt = -diff(Em,X1), dX2dt = -diff(Em,X2).
Any help is appreciated. Thank you!
2 Kommentare
Stephan
am 15 Mai 2018
Hi,
is it correct, that x and y are depending on t --> so: x(t) and y(t)?
Best regards
Stephan
Akzeptierte Antwort
Stephan
am 15 Mai 2018
Bearbeitet: Stephan
am 15 Mai 2018
Hi,
does this work for your purpose?
x1=0.3;
x3=0.9;
y1=0.4;
y3=0.8;
A=10;
p=10;
syms X_1 X_2 X1(t) X2(t);
num = ((x3-X_1)-(X_1-x1))*X_1 + ((y3-X_2)-(X_2-y1))*X_2;
den = sqrt((x3-X_1)-(X_1-x1)^2 + (y3-X_2)-(X_2-y1)^2);
Em = -A*(X_1-x1)*(x3-X_1) - A*(X_2-y1)*(y3-X_2) + p*num/den;
dEm_dX_1 = diff(Em,X_1);
dEm_dX_2 = diff(Em,X_2);
dEm_dX_1 = (subs(dEm_dX_1, [X_1 X_2], [X1 X2]));
dEm_dX_2 = (subs(dEm_dX_2, [X_1 X_2], [X1 X2]));
ode1 = diff(X1,t) == -dEm_dX_1;
ode2 = diff(X2,t) == -dEm_dX_2;
ode = matlabFunction([ode1; ode2])
ode is a function handle:
ode =
function_handle with value:
@(t)[diff(X1(t),t)==X1(t).*-2.0e1+(X1(t).*4.0e1-1.2e1).*1.0./sqrt(-X1(t)-X2(t)-(X2(t)-2.0./5.0).^2-(X1(t)-3.0./1.0e1).^2+1.7e1./1.0e1)+(X1(t).*2.0+2.0./5.0).*(X1(t).*(X1(t).*2.0-6.0./5.0).*1.0e1+X2(t).*(X2(t).*2.0-6.0./5.0).*1.0e1).*1.0./(-X1(t)-X2(t)-(X2(t)-2.0./5.0).^2-(X1(t)-3.0./1.0e1).^2+1.7e1./1.0e1).^(3.0./2.0).*(1.0./2.0)+1.2e1;diff(X2(t),t)==X2(t).*-2.0e1+(X2(t).*4.0e1-1.2e1).*1.0./sqrt(-X1(t)-X2(t)-(X2(t)-2.0./5.0).^2-(X1(t)-3.0./1.0e1).^2+1.7e1./1.0e1)+(X2(t).*2.0+1.0./5.0).*(X1(t).*(X1(t).*2.0-6.0./5.0).*1.0e1+X2(t).*(X2(t).*2.0-6.0./5.0).*1.0e1).*1.0./(-X1(t)-X2(t)-(X2(t)-2.0./5.0).^2-(X1(t)-3.0./1.0e1).^2+1.7e1./1.0e1).^(3.0./2.0).*(1.0./2.0)+1.2e1]
depending on time, which should be able to solve like you wanted to do.
Running it as a live script gives:
![](https://www.mathworks.com/matlabcentral/answers/uploaded_files/188508/image.png)
That's what you wanted to achieve?
Best regards
Stephan
5 Kommentare
Stephan
am 15 Mai 2018
Please note that i have assumed initial conditions:
X1(0)=0
X2(0)=0
You have to check this...i dont have an idea if this is correct.
Best regards
Stephan
Weitere Antworten (1)
Stephan
am 15 Mai 2018
Bearbeitet: Stephan
am 15 Mai 2018
Hi,
did i understand right:
x1=0.3;
x3=0.9;
y1=0.4;
y3=0.8;
A=10;
p=10;
syms X1 X2;
num = ((x3-X1)-(X1-x1))*X1 + ((y3-X2)-(X2-y1))*X2;
den = sqrt((x3-X1)-(X1-x1)^2 + (y3-X2)-(X2-y1)^2);
Em = -A*(X1-x1)*(x3-X1) - A*(X2-y1)*(y3-X2) + p*num/den;
dEm_dX1 = diff(Em,X1)
dEm_dX2 = diff(Em,X2)
dX1dt = -dEm_dX1
dX2dt = -dEm_dX2
This is what you wanted to do?
gives:
dX1dt =
(40*X1 - 12)/(17/10 - X2 - (X2 - 2/5)^2 - (X1 - 3/10)^2 - X1)^(1/2) - 20*X1 + ((2*X1 + 2/5)*(10*X1*(2*X1 - 6/5) + 10*X2*(2*X2 - 6/5)))/(2*(17/10 - X2 - (X2 - 2/5)^2 - (X1 - 3/10)^2 - X1)^(3/2)) + 12
dX2dt =
(40*X2 - 12)/(17/10 - X2 - (X2 - 2/5)^2 - (X1 - 3/10)^2 - X1)^(1/2) - 20*X2 + ((2*X2 + 1/5)*(10*X1*(2*X1 - 6/5) + 10*X2*(2*X2 - 6/5)))/(2*(17/10 - X2 - (X2 - 2/5)^2 - (X1 - 3/10)^2 - X1)^(3/2)) + 12
Can this be correct?
Best regards
Stephan
Siehe auch
Kategorien
Mehr zu Equation Solving finden Sie in Help Center und File Exchange
Community Treasure Hunt
Find the treasures in MATLAB Central and discover how the community can help you!
Start Hunting!